Classification of rigid pavement at airport taxiway using shear wave velocity and Elastic Modulus derived from Spectral Analysis of Surface Waves (SASW) method - Abdul Ghani, Nur Aina Farahana; Ismail, Norfarah Nadia; Wan Azahar, Wan Nur Aifa; Abd Rahman, Faridah; W. Azman, Amelia; Md. Yusoff, Nur Izzi; P. Rosyidi, Sri Atmaja (Springer, 2022)
Pavement assessment is significant in the maintenance and rehabilitation process. Spectral Analysis of Surface Waves (SASW) is one of the seismic testing where it is a non-destructive, inexpensive, convenient, and quick method to assess soil and rock mass characteristics as an alternative to the conventional method. Coring, which requires the drilling of the pavement, is the most popular practice. However, this method is not only disrupting the pavement condition but also time-consuming, expensive, and labor-intensive. Thus, this paper aims to use the SASW method to classify the pavement layers by evaluating the shear wave velocity and pavement modulus of rigid pavement of the taxiway at Kuala Lumpur International Airport (KLIA), Sepang. The measurement was done using two accelerometers acting as receivers and one impact hammer acting as a source on a taxiway site at KLIA. Based on the principle of stress waves that propagate through elastic elements, Rayleigh wave movements were monitored. The Rayleigh wave energy was generated using a set of transient impact sources with a variety of frequencies, and their potential to disperse across the surface layer of the pavement was explored which was applied in the SASW method. For the processing of the data taken at the field site, WinSASW software was used to mask the unprocessed data to get the dispersion curve which then obtained the shear wave velocity profile through the inversion process. The shear wave velocity was then used to determine the pavement modulus by using the equation developed by Yoder and Witczak. As a result, the shear wave velocity and modulus obtained for rigid taxiway in this research were between 1300 and 3000 m/s and 10 9 109 –60 9 109 Pa for the top layer (asphalt concrete) while 3000–3600 m/s and 60 9 109 –80 9 109 Pa for the second layer (cement-treated base). The SASW method has been proved to minimize labor, time, and expenses while delivering a quick and reliable outcome for a rigid pavement assessment without disrupting the pavement condition.